Penerapan Model Pembelajaran Inkuiri Berbasis Multikultural dalam Mata Pelajaran Ilmu Pengetahuan Sosial di Sekolah Dasar untuk Meningkatkan Toleransi dan Empati - Jamaludin Jamaludin (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine the implementation of a multicultural-based inquiry learning model in Social Studies instruction at the elementary school level and its impact on improving students’ tolerance and empathy. The research was conducted at SD Negeri Lung Manyo, Aceh Tamiang Regency, an elementary school with a culturally diverse student population. This study employed a qualitative descriptive approach. Data were collected through classroom observations, in-depth interviews, and documentation analysis. The findings reveal that the multicultural-based inquiry learning model was implemented through the stages of orientation, problem formulation, data collection, data analysis, and conclusion drawing by integrating cultural diversity values into the learning process. The implementation of this model positively influenced students’ tolerance, as reflected in their respect for differences, openness to diverse opinions, and ability to collaborate. Furthermore, students’ empathy also improved, as indicated by increased concern for others’ feelings, the ability to understand different perspectives, and more positive social behavior. The study concludes that the multicultural-based inquiry learning model is effective in fostering tolerance and empathy in elementary Social Studies learning.